POTTERY PRODUCTION AT THE SERVICE OF THE NECROPOLIS: On a suburban kiln in republican Gades (Cadiz, Spain) - Niveau de Villedary y Mariñas, Ana María (Rei Cretariae Romanae Fautorum Acta, 2024)
In recent years, one of the most important archaeological novelties in Cadiz has been the documentation of a dense cluster of pottery workshops on the third island of the palaeoarchipelago known in sources as Antipolis (today’s San Fernando), which, in the light of these discoveries, forms the “pottery district” of ancient Gadir. In contrast to documentation from San Fernando’s industrial quarter, the vestiges found in the city of Cadiz on the northern end of the island of Kotinussa are few and partial, yet not wholly unknown.